2018
DOI: 10.1038/s41467-018-07325-4
|View full text |Cite
|
Sign up to set email alerts
|

Effective connectivity of the anterior hippocampus predicts recollection confidence during natural memory retrieval

Abstract: Human interactions with the world are influenced by memories of recent events. This effect, often triggered by perceptual cues, occurs naturally and without conscious effort. However, the neuroscience of involuntary memory in a dynamic milieu has received much less attention than the mechanisms of voluntary retrieval with deliberate purpose. Here, we investigate the neural processes driven by naturalistic cues that relate to, and presumably trigger the retrieval of recent experiences. Viewing the continuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 67 publications
(111 reference statements)
2
39
0
Order By: Relevance
“…The first is the left precuneus, a key hub structure from the default mode network (DMN). The precuneus is engaged in self-related processing (Zhang and Chiang-shan, 2012), episodic memory (Ren et al, 2018), awareness and conscious information processing (Kjaer et al, 2001; Long et al, 2016; Vogt and Laureys, 2005). Also, it has been shown that patients with UWS having residual functional connectivity of DMN and external awareness networks might be misdiagnosed, since such functional connectivity is an indicator of covert consciousness (Naro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The first is the left precuneus, a key hub structure from the default mode network (DMN). The precuneus is engaged in self-related processing (Zhang and Chiang-shan, 2012), episodic memory (Ren et al, 2018), awareness and conscious information processing (Kjaer et al, 2001; Long et al, 2016; Vogt and Laureys, 2005). Also, it has been shown that patients with UWS having residual functional connectivity of DMN and external awareness networks might be misdiagnosed, since such functional connectivity is an indicator of covert consciousness (Naro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there is a scarcity of existing studies directly devoted to investigating the left versus right IPL in several different psychological tasks (see 42,43 for exceptions). The few existing studies committed to the effective connectivity of the IPL mainly focused on task-related connectivity changes between an IPL subregion and other areas of a specialized network for a single cognitive domain, typically in one hemisphere only 34,[44][45][46] . As such, our results usher towards a broader perspective.…”
Section: Causal Interactions Between Ipl Subregions Are Task Dependentmentioning
confidence: 99%
“…The first is the left precuneus, a key hub structure from the default mode network (DMN). The precuneus is engaged in self-related processing (Zhang and Chiang-shan, 2012), episodic memory (Ren et al, 2018), awareness and conscious information processing (Kjaer et al, 2001;Vogt and Laureys, 2005;Long et al, 2016). The second is a portion of the left orbitofrontal cortex, which is thought to encode predicted values of potential rewards (Gottfried et al, 2003).…”
Section: Low Integration In Doc Networkmentioning
confidence: 99%